The Practice of Religious Moderation Education in Primary Schools - Mohammad Arifan Adam Wahyudi Putra; Nur Azah (Journal Of Islamic Education And Pesantren, 2024)
This study aims to analyze the practice of religious moderation education through teacher modeling and habituation strategies in Islamic Religious Education (PAI) at SDN Sambirejo 1 Wonosalam Jombang. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation, and were analyzed thematically through data reduction, display, and conclusion drawing. The findings reveal that religious moderation is operationalized through two main pathways: the integration of moderation values within intracurricular activities (Islamic Religious Education, local religious content, Diniyah, and Civic Education) and reinforcement through cocurricular activities such as the Pancasila Student Profile Project, school habituation programs, and the actualization of school culture. Teacher modeling functions as moral legitimacy that facilitates the internalization of tawassuth (moderation), tasamuh (tolerance), and i’tidal (justice) through everyday performative attitudes and social interactions. Meanwhile, consistent habituation practices shape a moderate habitus among students, ensuring that tolerance and justice are not limited to cognitive understanding but become stable social behavior patterns. The study concludes that religious moderation is more effective when constructed as a school culture rather than merely as normative instructional content. The implications highlight the importance of a whole-school approach, strengthening teachers’ literacy on religious moderation, and integrating moderation values into the broader educational ecosystem. This research contributes to the development of a contextual, dialogical, and transformational pedagogical model of religious moderation in Islamic education.